Evaluation of Soil Degradation Due to Land Use Change Using Geospatial Analysis in the Ecological Zone of North Konawe Regency - Safiun; Widiatmaka; Dwi Putro Tejo Baskoro (Jurnal Penelitian Pendidikan IPA, 2026)
Land use change is one of the major factors affecting environmental quality, particularly soil degradation. North Konawe Regency has experienced rapid regional development characterized by the expansion of agricultural land, oil palm plantations, settlements, and mining activities. This study aimed to evaluate soil degradation caused by land use change in the ecological zone of North Konawe Regency during 2003, 2013, and 2023. The results showed that forest area decreased from 451,821.4 ha (88.0%) in 2003 to 432,564.5 ha (84.3%) in 2013 and further declined to 421,032.7 ha (82.0%) in 2023. The reduction of 30,788.7 ha of forest area indicates an increasing extent of degraded land due to land conversion. In contrast, oil palm plantations increased from 3,413.0 ha to 24,986.4 ha, while mining areas expanded from 424.3 ha to 12,463.2 ha. Converted lands, particularly mining areas, showed higher levels of soil degradation characterized by reduced soil porosity and permeability. The findings indicate that increasing land use intensity contributes directly to soil degradation in North Konawe Regency.